Improving Children's Health Quality With Posyandu in Somoketro Village, Magelang Regency During the Covid-19 Pandemic - Hayu Wardani Sati; Enny Fitriahadi; Vany Puspita Anggraeni; Yusitadika Arini; Dian Gita Cahyani (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Posyandu is a form of Community Based Health Efforts (UKBM) which is managed and organized from, by, for and with the community in the implementation of health development, in order to empower the community and provide convenience to the community in obtaining basic health services to accelerate the reduction of maternal mortality and morbidity baby. This community service examines the Implementation of Posyandu during the Covid-19 Pandemic in Semoketro II Hamlet, Somoketro Village, Salam District, Magelang Regency which aims to describe the implementation of Posyandu as an effort to improve the quality of children's health during the Covid-19 pandemic. This study uses descriptive qualitative methods and observation data collection techniques. Respondents in this community service are Posyandu cadres, medical personnel and Posyandu members. The results of community service show that the implementation of the Posyandu in Semoketro II village has fulfilled health protocols such as using masks, maintaining distance, washing hands with soap so that parents do not worry about doing Posyandu.